Η μάχη της καρέκλας ([object Object], 2015)
: I would like to say first that Orpheus was founded in 1905, in difficult times, and it was founded for national purposes. What do we want from this? Orpheus's purpose was to help liberate Poland. Difficult years passed, and 12 serais were found from all walks of life of professionals, from all social classes. There were doctors, doctors, coffee shops, and they were found in Kiosk. There were 12 young serais, and they decided to establish this association, Orpheus, to help liberate the serais and the law. They gave their souls to this cause. As soon as Orpheus was founded, all serais became members of Orpheus. The battle of Karekla is an event that is really worth remembering. It is worth reconnecting our memory with those times, because it is more useful to compare those days with today, because this movement of the battle of Karekla really connects us with the recent past and shows how the serais dealt with problems that we probably, if not certainly, still deal with today as a country. After the Second World War, an ungeneric effort of the serais began, in which Orpheus could not remain indifferent. Although the association seems to find its way, slowly but surely, to its center of activity, the problem of the expansion of the opened room remains a priority of the Delta Sigma, the Board of Directors. In June 1952, the conference we are going to talk about follows. The conference, therefore, the selection of events of general interest is carried out by means of transportation. In other words, according to the case, they carried seats from family centers of the city, such as Tselios, Edonia and others, and gave a small fee, or in other words, they carried them with their own hands, with their own dancers and members of the Board, as a generous gift from the other centers. However, this untapped situation had to end. As a result of the economic collapse of the association, and as a result of some of the threats of the problem, that is, the inexhaustible saving of the seats of Lifestone, will come in a completely obvious way. Let's move on to that time. The offer of the new seats to Orpheus by the same Serbs. Listen to a short excerpt from the previous newspaper. The battle of the chair. Beloved Serbs, sympathize. The historical Orpheus invites you to the battle of the chair. All of you were sent to his room by a chair. Let's see another excerpt. The room is unmoved, but it stands on its own, and in fact, it does not even have a seat. We think that it is not a big deal for a citizen to buy a seat and send it to Orpheus. On Friday, June 6, at 9.30 pm, after three months of preparation, the dances of the women, the men, and finally the night, 120 performers, please. There are also photos. They excite their friends and members of the association. The concert is resumed on June 15 at 11 am. And the words of the resumption are summarized in the publication of the Serb step on June 8, 1952. Christos Stamatio, we asked him live in our office a few years ago. In a discussion we had together, he mentioned this concert to me. It was moving. We saw the Serbs, much before the 11th, which was the concert, with the chairs in their hands, with the satisfaction of their faces, putting them in rows in the room. They ordered them to dance, with their own financial burden. In less than an hour, the room was transformed into a tightly packed, unknown hall. Imagine the performance of the choir. As if we had reached the end of the program, the Orphans clapped their hands and left, leaving about 600 seats free for the association. The reconstruction of the building took place. It was a very moving offering from the Serbian citizens. I would like to tell you about an incident that took place on the street. I am very moved now. There was a girl on the street, a 13-year-old girl, who called out, Mrs. Spiridra, aren't you the president of Orpheus? I said, yes, my dear. She lowered her eyes, and the boy was a 20-year-old. I said, what is this? I want to help the Orphan, and he didn't stand up. He was on a piece of paper, and he didn't stand up to ask, what's the name of the child? He was afraid that I would misunderstand him, because he was young. But this 20-year-old was worth the thousands of adults, because the child was delayed. I felt very much at ease with the Serbs who helped us in this crisis. On October 29, 2012, we held the inauguration. I said a few words, and while I was speaking, it was as if I saw the heroes of 1905, the Macedonian fighters, joining the Serbs of today, the servants of culture, joining with joy, with the same feelings of creation, of the Serbs who gave their blood and heart to build the building, and of today's Serbs who gave their delay to restore the building. It was an experience that moved me. I felt deep inside me at that time, and I lived different moments. The Serbs of today, on October 29, 2012, we held the inauguration. I felt very much at ease with the Serbs who helped us in this crisis. I felt very much at ease with the Serbs who gave their blood and heart to build the building, and of today's Serbs who gave their delay to restore the building. I felt very much at ease with the Serbs who helped us in this crisis.